Polyglotism and Identity in Modern-Day Lebanon - Baladi, Sarya Sofia (Lingua Frankly, 2018)
Lebanon is a polyglot country, where Western languages such as English or French, or more traditional/oriental languages such as Classical Arabic, have much societal and political power. Although all Lebanese speak Levantine Arabic (Shaami), many of them master multiple languages and can decide to strongly identify with a select few not only for the love of the language, but mostly for the message each language brings with it: is Lebanon a cosmopolitan Westernized country that differentiates itself from the Arab world? Or should Lebanon look towards its Oriental roots and celebrate its Muslim-Arabic heritage? This paper seeks to prove that, in Lebanon, the implicit or explicit choice of language is a tool to convey one’s political, religious, and cultural views. This created a strong divide between Eastern and Western oriented Lebanese in the 20th century and is one of the main causes for the political turmoil in modern Lebanon.